A Process Model for Clinical Decision Making in High-Risk Outpatient Situations: The Therapeutic Alliance and Suicide - Truscott, Derek; Evans, Jim; Knish, Steve (Canadian Journal of Counselling and Psychotherapy, 2007)
When a client is at risk for suicide, important counselling decisions must be made. In this article we present a process model for decision making in high-risk outpatient situations. We propose that counsellors attend to two key dimensions of these situations: the strength of the therapeutic alliance and the degree of suicide risk. Therapeutic actions are then directed toward strengthening the alliance, and toward implementing other risk-reduction interventions only when the risk cannot be adequately reduced via the alliance. Four case studies are presented to illustrate the application of the model to suicidal situations.